Training-related sports injury patterns among elite middle and high school field hockey players in Korea - Choi, M.; Lee, K. (Sports, 2025)
This study aimed to analyze the incidence, affected areas, and types of injuries sustained during training among youth field hockey players to identify key characteristics. A survey was conducted with 374 youth field hockey players (236 males, 138 females) from middle and high school teams registered with the Korea Hockey Association in 2024. Data were collected on injury status, training hours, injury sites, and prevention methods. Chi-square tests, independent t-tests, and frequency analyses were performed to assess differences in injury incidence based on gender and school level. The analysis revealed no significant gender differences in training-related injury experiences, with 17.2% of male athletes and 10.2% of female athletes reporting injuries during training. Similarly, no significant difference was found between middle and high school athletes, although high school athletes had a significantly lower injury incidence than middle school athletes (1.54 vs. 2.28 per 1000 h, p < 0.05). The most common injury sites were the ankle and knee, with muscle injuries being the most frequent among males and ligament injuries among females. Additionally, male and high school athletes more frequently reported engaging in warm-up and cool-down exercises. There was no significant difference in injury rates between genders during training, but high school athletes tended to experience fewer injuries than middle school athletes. Ankle injuries were the most common, with muscle and ligament damage being the primary types of injuries. While warm-up exercises were commonly practiced, further research is needed to determine their actual effectiveness in injury prevention.